1957
DOI: 10.1079/bjn19570046
|View full text |Cite
|
Sign up to set email alerts
|

Volatile fatty acids and lactic acid in the rumen of dairy cows receiving a variety of diets

Abstract: It has been known for many years that organic acids are produced by bacterial fermentation in the rumen. T h e importance of such fermentation in the nutrition of the ruminant has been adequately appreciated only recently, with the establishment of the relative proportions in which the acids are produced and the discovery of their role in ruminant metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
67
2
1

Year Published

1959
1959
1992
1992

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 147 publications
(84 citation statements)
references
References 27 publications
(10 reference statements)
14
67
2
1
Order By: Relevance
“…However, acid production tended to be higher at two hours after feeding with long hay. In contrast, Meyer et al (1959a) found a faster breakdown of holocellulose accompanied by increased acid and carbon dioxide production one and onehalf and four hours after feeding of pelleted hay as compared to chopped hay, Balch and Rowland (1957) reported a more rapid rate of fatty acid formation when the hay was finely ground.…”
Section: Performance Of Faunated and Protozoa-free Lambsmentioning
confidence: 84%
See 4 more Smart Citations
“…However, acid production tended to be higher at two hours after feeding with long hay. In contrast, Meyer et al (1959a) found a faster breakdown of holocellulose accompanied by increased acid and carbon dioxide production one and onehalf and four hours after feeding of pelleted hay as compared to chopped hay, Balch and Rowland (1957) reported a more rapid rate of fatty acid formation when the hay was finely ground.…”
Section: Performance Of Faunated and Protozoa-free Lambsmentioning
confidence: 84%
“…On the other hand, Balch and Rowland (1957) found a narrower ratio of acetate to propionate as the rate of fer mentation in the rumen increased. The relative proportions of fatty acids in the rumen at a given time may not be an indication of their formation since the processes of absorp-tlon continually remove them from the rumen.…”
Section: Coz (19^8) Summarized Seven Experiments In Which Lambsmentioning
confidence: 90%
See 3 more Smart Citations